POLITIK ANGGARAN DINAS PEKERJAAN UMUM, TATA RUANG, PERUMAHAN RAKYAT DAN KAWASAN PERMUKIMAN KABUPATEN SIAK DALAM PEMBANGUNAN INFRASTRUKTUR JALAN TAHUN 2020 (Studi Kasus Jl. Pelimauan Desa Teluk Merempan) - Ulfa, Munifasarah; ", Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The streets in Siak Regency are currently quite a lot of people admire. A lot of damage to a road segment, ranging from damage in the form of cracks, bumps, potholes and even a lot of heaps of gravel and dirt roads. And one of them is the Pelimauan road which is the main road that connects the Teluk Merempan villages with Merempan Hilir with a length of 2.699 km with a construction of 540 m of gravel pavement, 1.160 m of peat or soft soil roads and 999 m of sand roads. With the condition of the road when it rains, the condition will become very slippery and flooded with water so that it can endanger motorists who cross the road.This study aims to see how the budget from the Department of Public Works, Spatial Planning, Public Housing and Settlement Areas in the construction of the Pemlimauan road infrastructure in Teluk Merempan Village, Merempan District, Siak Regency in 2020. This study uses a qualitative descriptive approach. Then the data collection techniques used are interviews, observation and documentation. While the data analysis technique is done by collecting information through interviews, data reduction and data presentation.The results of the study found that in improving the Pemlimauan Teluk Merempan Village Road in 2020. With the theory of Thompson and McEwen (2006) it is known that bargaining, co-optation and coalition factors are the result of "musrembang" and "recess" to formulate 2020 APBD budget policies that will went well and gave birth to a solution due to limited APBD funds. The factors that hinder the rapid realization of the Pelimaanu road improvement program in Teluk Merempam Village are limited budget, poor communication and public awareness of infrastructure maintenance. Keywords: Budget Politics, Development, Infrastructure and Roads